2021
DOI: 10.48550/arxiv.2107.00834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No-Hair Theorem in the Wake of Event Horizon Telescope

Mohsen Khodadi,
Gaetano Lambiase,
David F. Mota

Abstract: Thanks to the release of the extraordinary EHT image of shadow attributed to the M87* supermassive black hole (SMBH), we have a novel window to assess the validity of fundamental physics in the strong-field regime. Motivated by this, we consider Johannsen & Psaltis metric parameterized by mass, spin and an additional dimensionless hair parameter which in the high rotation regimes is able to provide a suitable framework for the test of the no-hair theorem (NHT) using the EHT data. Incorporating the into the sta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 83 publications
(92 reference statements)
1
15
0
Order By: Relevance
“…These observations are consistent with the image of Kerr black hole predicted from GR, but they cannot rule out Kerr or non-Kerr black holes in MoG. Thus, the EHT observations of shadow are then applied as an important tool to test black hole in strong gravitational field regime, as the observational data could be used to constrain the black hole parameters in MoG, and even to distinguish different theories of gravity [46][47][48][49][50][51][52][58][59][60].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…These observations are consistent with the image of Kerr black hole predicted from GR, but they cannot rule out Kerr or non-Kerr black holes in MoG. Thus, the EHT observations of shadow are then applied as an important tool to test black hole in strong gravitational field regime, as the observational data could be used to constrain the black hole parameters in MoG, and even to distinguish different theories of gravity [46][47][48][49][50][51][52][58][59][60].…”
Section: Introductionmentioning
confidence: 83%
“…Thus, physicists could use shadow to unreveal the near horizon features of black hole by analytical investigations or numerical simulation of their shadows and therein. Moreover, the size and distortion of shadow [31,32], which could be calculated via the boundary of shadow, has been widely investigated to estimate the black hole parameters in both GR and MoG, with or without additional sources surrounding the black hole [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. This direction could be seen as one aspect of black hole shadows to distinguish GR and other theories of gravity, or to acquire the information of the surrounding matter, though it was found that those theoretical features of shadow are usually not sufficient to distinguish black holes in different theories or confirm the details of the surrounding matter.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the role of electric charge on the BZ mechanism has been investigated recently in [68,69]. Theoretically, considering the contribution of electric charge is well motivated from several aspects: first, according to the no-hair theorem, any astrophysical BH described by three observable parameters-mass, spin, and electric charge [70,71]. Second, unlike the argument that the presence of plasmas around astrophysical BHs leads to a prompt discharge, the relevant environment is prone to some processes at both the classical and relativistic levels that result in the production of a small nonzero electric charge [72].…”
Section: Discussionmentioning
confidence: 99%
“…Due to this property, the shape of the capturecross-section by light is transformed into an asymmetric one. An interesting astrophysical phenomenon is that the shadow of a rotating black hole has the asymmetric bright side due to this property [43,44,45,46,47,48,49,50,51,52,53,54].…”
Section: Energy Extraction From a Rotating Black Holementioning
confidence: 99%